Mapping of Government’s Communication Strategies in the COVID-19 Era on Social Media - Hasti, Iyomi; Qodir, Zuly (Journal of Governance and Public Policy, 2024)
This study explores the changing government communication methods throughout the unusual COVID-19 epidemic, with a focus on using social media as the main instrument for engaging with the public. We utilize a bibliometric methodology, examining an extensive dataset of articles obtained from journals indexed in Scopus. Using VOSviewer software, we provide a visual representation of the main theme clusters in this research. NVivo 12 Plus also supports word cloud analysis, which allows for the discovery of commonly used phrases and patterns within the analyzed material. The results of study reveals a range of communication strategies adopted by governments globally in response to the pandemic. These measures involve promoting communication in both directions, utilizing social media platforms to spread information, and using efficient strategies to communicate risks. The data demonstrates a predominance of research that specifically examines risk communication driven by the government, emphasizing its vital role in crisis management. In addition, the VOSviewer mapping reveals the presence of four unique theme clusters. The "government communication" cluster focuses on subjects such as communication strategy, the ongoing epidemic, the challenge of fake news, and the influence on public anxiety. These areas are key to the research and investigation within this cluster. This comprehensive analysis illuminates the complex correlation between social media communication techniques and successful public health actions amidst a worldwide crisis.